The Detection of Breast Cancer for Young Woman in Covalima Municipality, Republica Democratica de Timor Leste - Joaquim Pinto; Maria Manuela da Conceicao Alves; Ostelino da Silva Belo; Alexandra Maria Pires; Manuel da Costa Fernandes; Jose Ximenes da Conceicao; Teresa de Jesus Vaz Cabral; Aida Gusmao (Rifa'Institute, 2022)
Introduction: According to the World Health Organization, there are 2.3 million breast cancer diagnoses and globally 685,000 breast cancer mortality rates. In 2020 women who have had problems with breast cancer are 7.8 million annually worldwide. A study by the Global International Agency for Research of Cancer (2018) reported that the highest number of breast cancer cases was 674,693, with 25.5% and a mortality rate of 310.577 or 13.8%. And continues to be published by the Global Cancer Observatory (2019), showing that the incidence of breast cancer is 136.2% of the population, and the highest rate of breast cancer occurs in women with 42.1%, followed by population mortality. Objective: To find out how to detect breast cancer in adolescent girls in Covalima City, Timor Leste. Method: This study used quantitative and quantitative methods together, specifically a cross-sectional study of adolescent girls in the municipality of Covalima where interviews with young girls continued their studies in secondary schools. Results: Based on the results of research conducted by young women in high schools in the city, the understanding of describing early detection of breast cancer is 49%, and most young women know information about breast cancer even though the information they have is accessed or someone shares about breast cancer. Conclusion: Students have sufficient experience in how to detect breast cancer early and prevent breast cancer